2019
DOI: 10.1016/j.adaj.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Preventive dental care use for children with special health care needs in Washington's Access to Baby and Child Dentistry program

Abstract: Background. Low-income, preschool-aged children with special health care needs (CSHCN) are at increased risk for poor oral health. The study goal was to assess preventive dental care use for Medicaid-enrolled CSHCN within Washington state’s Access to Baby and Child Dentistry (ABCD) Program. Methods. We analyzed 2012 Medicaid eligibility and claims files for children under age 6 years in the ABCD Program (N=206,488). Medical diagnosis and eligibility data were used to identify each child’s special needs statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…This finding revealed an interplay between medical and dental conditions, which is consistent with previous findings. Craig et al found that children with special healthcare needs ( SHCN ) had more caries and were less likely to use preventative dental care ( 19 , 36 ). SHCN has been classified as a moderate risk for dental caries in children at 0–5 years ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding revealed an interplay between medical and dental conditions, which is consistent with previous findings. Craig et al found that children with special healthcare needs ( SHCN ) had more caries and were less likely to use preventative dental care ( 19 , 36 ). SHCN has been classified as a moderate risk for dental caries in children at 0–5 years ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding ECDC utilization patterns is the first step in developing future interventions to prevent early childhood caries and reduce dental costs. Prior studies that examined ECDC utilization patterns have relied exclusively on supervised machine learning methods (e.g., logistic regression) where target outcomes are predefined (e.g., preventive dental care use, yes or no) ( 17 19 ). While supervised machine learning is popular and useful in examining relationships between predefined variables, they are incapable of uncovering meaningful hidden patterns that cannot be detected using predefined variables.…”
Section: Introductionmentioning
confidence: 99%
“…First, caregivers of children with ASD need to be educated that their children have a greater odds of having dental caries. Second, children with ASD are in greater need of early access to preventive dental services due to the greater odds of having dental caries (Brickhouse et al 2009;Chi et al 2016;Craig et al 2019). In this study, approximately 86% of children with and without ASD received preventive dental care in the past year.…”
Section: Discussionmentioning
confidence: 68%
“…For example, we controlled for the child's use of preventive oral health care services because parents of children with ASD reported greater barriers to accessing care in the dental office as compared with their typically developing peers (Newacheck et al 2000;L.I. Stein et al 2012) and children with special health care needs were significantly less likely to use preventive dental care than children without special health care needs (Craig et al 2019).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…10,11 A more recent study reported that Medicaid-enrolled CSHCN under age 6 years were significantly less likely to utilize preventive dental care than children without SHCN (prevalence rate ratio: 0.91; 95% CI: 0.88, 0.94; P < .001). 12 This may be because of differential barriers to dental care encountered by CSHCN. Paediatric dentists are maldistributed and general dentists may not feel sufficiently trained to treat medically complex CSHCN.…”
mentioning
confidence: 99%